Evaluation of hydrogen permeation rate through zirconium pipe. (August 2018) - Katayama, Kazunari; Izumino, Jyunichi; Matsuura, Hideaki; Fukada, Satoshi
Highlights: Tritium confinement by a multilayer structure of Zr and Al2 O3 was proposed. Hydrogen permeation experiments for two samples of Zr pipe were conducted. Hydrogen permeation rate through one Zr pipe is proportional to a square root ofhydrogen pressure. Hydrogen permeation rate through another Zr pipe did not depend on hydrogen pressure. Hydrogen permeability and diffusivity in Zr pipe were larger than that in Al2 O3 . Abstract: To launch a fusion reactor stably, it is necessary to prepare sufficient amount of tritium by an external tritium source. Tritium production using nuclear reactions by neutron and Li in a high temperature gas-cooled reactor (HTGR) is an attractive method. An important issue is tritium confinement in high temperature conditions of HTGR. Covering Li compound by Al2 O3 is a promising method because hydrogen permeability in Al2 O3 is quite low. Furthermore, it is expected that inserting Zr between Li compound and Al2 O3 suppresses tritium permeation because Zr has a large hydrogen absorption capacity. For example, a cylindrical multilayer structure consisted of Zr – Li compound – Zr – Al2 O3 is a candidate structure to confine generated tritium. To evaluate hydrogen permeation rate through cylindrical Zr material, in this work, hydrogen permeation experiments were carried out for two samples of one-side sealed Zr pipe. Hydrogen permeation rate in one sample was proportional to as the square root of hydrogen pressure but that in another sample, which had retained a certain amount of hydrogen before the experiment, did not indicate an obvious pressure dependence regardless of almost the same experimental procedure except hydrogen permeation direction. Since observed hydrogen permeation rate in Zr was faster than that in Al2 O3, under the multi confinement structure by Zr – Li compound – Zr – Al2 O3, the generated tritium in Li compound diffuses promptly in whole Zr inside Al2 O3 layer and it is expected tritium is stored stably in the structure.